2017
DOI: 10.1016/j.celrep.2017.10.080
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Fixation Redefines Quiescence and Early Activation of Skeletal Muscle Stem Cells

Abstract: State of the art techniques have been developed to isolate and analyze cells from various tissues, aiming to capture their in vivo state. However, the majority of cell isolation protocols involve lengthy mechanical and enzymatic dissociation steps followed by flow cytometry, exposing cells to stress and disrupting their physiological niche. Focusing on adult skeletal muscle stem cells, we have developed a protocol that circumvents the impact of isolation procedures and captures cells in their native quiescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
322
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 246 publications
(385 citation statements)
references
References 42 publications
(48 reference statements)
18
322
0
3
Order By: Relevance
“…Regardless of whether FACS is used, optimization of enzymatic digestion conditions for cell viability and yield is critical, as in our experience this represents the most common point of experimental failure in scRNA‐seq studies. In keeping with this, comparison of in vivo transcriptional profiles on fixed cells to cells undergoing a typical isolation protocol in muscle suggests that enzymatic digestion is the major step that can disrupt the in vivo transcriptional profile . This emphasizes the importance of minimizing the duration and harshness of enzymatic digestion, and we note that brief digestion protocols can provide robust yields of mesenchymal cells, particularly in younger mice .…”
Section: Planning a Scrna‐seq Study Of Bonesupporting
confidence: 56%
See 3 more Smart Citations
“…Regardless of whether FACS is used, optimization of enzymatic digestion conditions for cell viability and yield is critical, as in our experience this represents the most common point of experimental failure in scRNA‐seq studies. In keeping with this, comparison of in vivo transcriptional profiles on fixed cells to cells undergoing a typical isolation protocol in muscle suggests that enzymatic digestion is the major step that can disrupt the in vivo transcriptional profile . This emphasizes the importance of minimizing the duration and harshness of enzymatic digestion, and we note that brief digestion protocols can provide robust yields of mesenchymal cells, particularly in younger mice .…”
Section: Planning a Scrna‐seq Study Of Bonesupporting
confidence: 56%
“…This emphasizes the importance of minimizing the duration and harshness of enzymatic digestion, and we note that brief digestion protocols can provide robust yields of mesenchymal cells, particularly in younger mice . Alternatively, there are several approaches designed to circumvent isolation‐associated artifacts, including in vivo fixation before cell isolation, though fixation can negatively impact cell isolation efficiency and RNA quality . In another approach, transgenic expression of Toxoplasma gondii uracil phosphoribosyltransferase (UPRT) only in cell types of interest allows for selective labeling, capture, and bulk sequencing of transcripts only from this cell type after whole‐tissue RNA extraction .…”
Section: Planning a Scrna‐seq Study Of Bonementioning
confidence: 99%
See 2 more Smart Citations
“…On FACS plots, we found that the freshly isolated p110α ‐null MuSCs were even smaller in size than the control MuSCs based on the mean forward scatter (FSC) values (Fig EV4C). This was most likely due to the fact that the control “MuSCs” was already partially activated during the isolation process (van den Brink et al , ; Machado et al , ; van Velthoven et al , ). Consistently, on freshly isolated myofibers, we found that the size of the mutant MuSCs was indeed smaller than that of the control MuSCs (Fig EV4D and E).…”
Section: Resultsmentioning
confidence: 99%